Underemployment in Malaysia: how education quality contributes to the challenges and issues / Nor Sabrina Zahari and Mohd Fahmi Zahari - Zahari, Nor Sabrina; Zahari, Mohd Fahmi (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Underemployment is a situation where individuals are employed but not fully utilized in their jobs, often due to working fewer hours than desired or being in positions that don't match their skills or education level. Highlights job quality and individuals' dissatisfaction with their employment due to factors like being overqualified for their current role. For example, someone with a bachelor's degree who only manages to secure a job meant for an STPM graduate. Despite the skills and qualifications, they may possess, many young people struggle to find jobs that match their level of education or experience, leading to underemployment or even prolonged unemployment. The issue is compounded by various factors. Does this underemployment problem prove that the quality of education in Malaysia is still at a low level? Several key indicators and pieces of evidence support the notion that the education system in Malaysia is of high quality. Every year there is an increase in the number of graduates in Malaysia.